Spatially periodic states in a strongly dipolar Dy164-Dy162 mixture - Adhikari, S. K. [UNESP] (American Physical Society (APS), 2025)
We demonstrate the formation of a novel eigenstate in a strongly dipolar binary Dy164-Dy162 mixture, where the inter- and intraspecies dipolar lengths are larger than the corresponding scattering lengths. When this mixture is confined by a quasi-two-dimensional harmonic trap, the total density exhibits the formation of droplets on a spatially symmetric triangular or square lattice, where each droplet is formed of a single species of atoms; two types of atoms never exist on the same lattice site. The density of any of the species shows a partially filled incomplete lattice; only the total density exhibits a completely full lattice structure. In this theoretical investigation we employ the numerical solution of an improved mean-field model including a Lee-Huang-Yang-type interaction in the intraspecies components alone, meant to stop a collapse of the atoms at high atom density.